On the rocky road to efficient behavior management: Can emotional competencies signal the better way? - Gay, Philippe; Genoud, Philippe A.; Kappeler, Gabriel; Cuozzo, Marilena; Gomez, Jean-Marc; Bapst, Malika S.; Fiori, Marina (Frontiers in Psychology, 2022)
Classroom management is a key issue for teachers, while emotional competence is a major contributor to professional success and sustainability in this profession. The investigation of the multifaceted nature of these two constructs may be important in order to take a step towards understanding which emotional competence could foster specific aspects of classroom mastery. To explore this issue, elementary school teachers (N = 121, 1st-4th grades) answered the Profile of Emotional Competence, which comprises 12 scores of emotional competencies, and a four-dimensional self-efficacy scale for behavior management in the classroom. Results indicate that intrapersonal emotional competencies, as compared to interpersonal competencies, play a major role regarding self-efficacy beliefs. In particular, higher identification of personal emotions was associated with better perceived self-efficacy on the four aspects of classroom management. In addition, regulation of one’s emotion predicted proactive management, understanding of one’s emotions predicted reactive management, and using other’s emotions predicted proactive involvement of the pupil's parent or caregiver. Results are discussed in terms of their contribution to research in educational sciences and in teacher education, particularly with respect to teachers' sustainability in the profession.